“While Quirinius was governing Syria”: Towards the historical plausibility of Luke 2:2 - de Oliveira Neto, Maviael Alves (Kerygma, 2022)
The present paper employs a historiographical comparative approach to evaluate the historical plausibility of the census found in Luke 2:2. Though there is no direct evidence of a census under Quirinius, in Judea, before the death of Herod other than Luke 2:2, nevertheless there is enough evidence to state Luke’s historical plausibility when the larger context is considered, i.e. the nature of roman censuses, the Egyptian census system, the accounts of Josephus, Herod’s relationship with Rome, the identity and career of Quirinius and a recent archaeological discovery of a roman weight standard in Herods’ Judea.